2022
DOI: 10.3390/diagnostics12020479
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption and the Risk of Incident Atrial Fibrillation: A Meta-Analysis

Abstract: Alcohol consumption is a known, modifiable risk factor for incident atrial fibrillation (AF). However, it remains unclear whether the protective effect of moderate alcohol consumption-that has been reported for various cardiovascular diseases also applies to the risk for new-onset AF. The purpose of this meta-analysis was to evaluate the role of different drinking patterns (low: <14 grams/week; moderate: <168 grams/week; and heavy: >168 grams/week) on the risk for incident AF. Major electronic databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…In the Women’s Health Study with 34,715 healthy, middle-aged women consumption of more than two drinks per day significantly increased the risk of incident AF, whereas consumption of less than two drinks a day did not [ 213 ]. These findings are supported by a recent meta-analysis suggesting a J-shaped relationship between the amount of alcohol intake and incident AF [ 221 ].…”
Section: Atrial Myocardium and Alcoholsupporting
confidence: 77%
See 1 more Smart Citation
“…In the Women’s Health Study with 34,715 healthy, middle-aged women consumption of more than two drinks per day significantly increased the risk of incident AF, whereas consumption of less than two drinks a day did not [ 213 ]. These findings are supported by a recent meta-analysis suggesting a J-shaped relationship between the amount of alcohol intake and incident AF [ 221 ].…”
Section: Atrial Myocardium and Alcoholsupporting
confidence: 77%
“…Numerous large cohort studies have since confirmed an association between alcohol consumption and incident AF [ 210 , 211 , 212 , 213 , 214 , 215 , 216 ]. Meta-analyses give a thorough overview over the extensive literature regarding the association between alcohol and AF [ 216 , 217 , 218 , 219 , 220 , 221 ].…”
Section: Atrial Myocardium and Alcoholmentioning
confidence: 99%
“…Alcohol use is associated with increased risk of cardiovascular disease and cardiovascular disease risk factors [37]. The increased cardiovascular risk generally follows a J-shaped dose-dependent relationship with lower risk with moderate consumption of two standard drinks per day [37,38]. This J-shaped dose-dependent relationship can be seen in hypertension, dyslipidaemia, insulin resistance, myocardial infarction (MI), cerebrovascular accident (CVA) and atrial fibrillation (AF) [37,38].…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…The increased cardiovascular risk generally follows a J-shaped dose-dependent relationship with lower risk with moderate consumption of two standard drinks per day [37,38]. This J-shaped dose-dependent relationship can be seen in hypertension, dyslipidaemia, insulin resistance, myocardial infarction (MI), cerebrovascular accident (CVA) and atrial fibrillation (AF) [37,38]. The risk of cardiovascular disease including major adverse cardiac events is increased for patients with severe psoriasis [7].…”
Section: Cardiovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation